Expression, Localization, and Effect of High Salt Intake on Electroneutral Na+/HCO3– Cotransporter NBCn2 in Rat Small Intestine: Implication in Intestinal NaCl Absorption - Wang, Jin-Lin; Zhao, Lei; Zhu, Jun; Wang, Deng-Ke; Ren, Mei-Juan; Wang, Meng; Liu, Ying; Boron, Walter F.; Chen, Li-Ming (Frontiers in Physiology, 2019)
The electroneutral Na+/HCO3– cotransporter NBCn2 (SLC4A10) of solute carrier family 4 (SLC4) plays important physiological and pathological roles in the body. Our previous study showed that NBCn2 is expressed on the protein level in the small intestine of rat. Here, by reverse-transcription polymerase chain reaction, we identified a novel full-length NBCn2 variant, i.e., NBCn2-K, from rat small intestine. By pHi measurement with Xenopus oocytes, the activity of NBCn2-K is not significantly different from NBCn2-G. By western blotting, NBCn2 and the Na+/H+ exchanger NHE3 (SLC9A3) are predominantly expressed in the jejunum of rat small intestine. By immunofluorescence, NBCn2 and NHE3 are localized at the apical domain of the jejunum. NaCl overload decreases the expression of NBCn2 by 56% and that of NHE3 by 40% in the small intestine. We propose that NBCn2 is involved in the transepithelial NaCl absorption in the small intestine, and that the down-regulation of NBCn2 by NaCl represents an adaptive response to high salt intake in rat.